1971
DOI: 10.1104/pp.48.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Respiratory Response of Fig (Ficus carica L. cv. Mission) Fruits to Ethylene

Abstract: Maxie and Crane (37) pointed out that "Before CMH can be established as a growth regulator in figs, it must be verified that production of the gas is correlated with the onset of renewed growth (Period III)." Evidence indicating the existence of such a correlation is presented here. MATERIALS AND METHODSCurves of growth in diameter were developed for both firstand second-crop fruits and were used for reference in timing of ethylene treatment and in fruit sampling. Diameters of 10 basal-most fruits on each of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
3

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 21 publications
(16 reference statements)
4
49
0
3
Order By: Relevance
“…A sharp rise in respiratory activity was noted after 24 hr of exposure to ethylene in vivo (7). Changes in color, texture, and an increase in fruit (7) and cell size (N. Marei and M. Bradley, in preparation) were first detected after 48 hr of continuous treatment.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…A sharp rise in respiratory activity was noted after 24 hr of exposure to ethylene in vivo (7). Changes in color, texture, and an increase in fruit (7) and cell size (N. Marei and M. Bradley, in preparation) were first detected after 48 hr of continuous treatment.…”
Section: Methodsmentioning
confidence: 97%
“…Mission) fruits were sampled periodically during growth period II and following ethylene treatments (7). Ethylene (5 ul/liter in an air mixture with a flow rate of 100 ml/min) was applied to fruits still on the tree (in vivo treatment) using the procedure of Marei and Crane (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suge (47) found that a low concentration of ethylene stimulated growth of intact oat and rice mesocotyls. Hirai et al (14), Maxie and Crane (30), and recently Marei and Crane (29) showed that ethylene markedly stimulated the enlargement and maturing of immature fig fruits. These are particularly germane observations, since fig ripening is the only other well substantiated situation in which lipids induce ethylene formation (13,14), and the fig fruit is anatomically derived from a stem.…”
Section: Substratementioning
confidence: 99%